Penerapan Model Cooperative Tipe Number Head Together (NHT) Berbantuan Media Visual Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas IV SD Negeri 2 Nongan - Suciarmini, Ni Made; Suardana, I Putu Oka; Sudirman, I Nyoman (Dharmas Education Journal (DE_Journal), 2025)
This study aims to improve the learning outcomes of natural science or science of grade 4 students of SD Negeri 2 Nongan by implementing a cooperative learning model of the number head together type or which can be abbreviated as nht and using visual media assistance. This study began with the low learning outcomes of students which can be seen from their test scores which are still below the achievement criteria. By using visual media assistance about the form of matter and also its changes in the first cycle, the initial action was carried out by grouping young students where the researcher used one image media to discuss material related to the form of matter and also its changes. The evaluation results showed that the completeness of student learning outcomes was still relatively low where the average value was only 6. In the second cycle which was carried out using larger media and also comparing student worksheets or which can be abbreviated as LKPD, this showed that there was an increase in the average science learning outcomes to 83.5 with classical completeness reaching 88.2%, which exceeded the maximum completeness value of 80%, therefore the researcher concluded that using the NHT model was very effective in encouraging student motivation to be able to increase their self-confidence and be able to improve understanding of the material and also be able to improve student learning outcomes.